PENGARUH MEDIA MASSA TERHADAP GENERASI Z SEBAGAI PARTISIPASI PEMILU 2024 : DI TINJAU DARI TEORI DEMOKRASI - Lananda, Ardelia; Mulyadi, Dedi; Simbolon, Cindy Claudia; Alvian M.S, Ce Kedzma; Farraz, Mohammad Irvanul; Perdana, Zaki Akhtar (RIO LAW JURNAL, 2024)
Mass media in political activities such as presidential elections and legislative elections can have quite a big influence. This is because Generation Z is a mass media user, which makes this generation one of the generations that actively participates in presidential and legislative elections. The aim of this research is to analyze in more depth the influence of mass media on generation Z in participating in the 2024 election, in terms of democratic theory. The approach method in this research is to use a normative juridical approach, namely a legal research method that examines library materials or secondary data. One of the influences of the mass media on presidential elections and legislative elections is that it can influence the number of votes. This is because generation Z is a large group of voters and has the potential to influence election results. With active participation from generation Z, they can change political direction and elect leaders who can represent the values and interests of generation Z.